DDDR-31. THE THERAPEUTIC POTENTIAL OF THE LONG NON-CODING RNA LNC-HLX-2-7 IN GROUP 3 MEDULLOBLASTOMAS IN CHILDREN. (14th November 2022) - Katsushima, Keisuke; Yuan, Menglang; Lee, Bongyong; Stapleton, Stacie; Jallo, George; Seal, Sudipta; Eberhart, Charles; Perera, Ranjan
Abstract: Medulloblastoma (MB) is an aggressive brain tumor that predominantly affects children. Recent high-throughput sequencing studies suggest that the non-coding RNA genome, in particular long non-coding RNAs (lncRNAs), contributes to MB formation and tumor progression. Here we report the identification of a novel lncRNA, lnc-HLX-2-7, as a potential therapeutic target in group 3 MBs. In this study, we report that lnc-HLX-2-7 RNA specifically accumulates in the HLX (host gene of lnc-HLX-2-7 ) promoter region and activates HLX expression by recruiting multiple factors including enhancer elements. RNA sequencing and chromatin immunoprecipitation revealed that HLX directly binds to the promoters of several tumor-promoting genes, including MYC, and activates their expression. Furthermore, intravenous treatment with antisense oligonucleotides targeting lnc-HLX-2-7 coated with cerium-oxide nanoparticle (CNP- lnc-HLX-2-7 ) reduced tumor growth (40-50%) in intracranial MB xenograft mouse model (n = 10, p < 0.01, t-test). We found that the combinatorial therapy of CNP- lnc-HLX-2-7 and cisplatin further inhibits tumor growth and significantly prolongs mouse survival compared to CNP- lnc-HLX-2-7 monotherapy (n = 10, p < 0.01, t-test) only. We report here the importance of the lnc-HLX-2-7-HLX-MYC axis in regulating group 3 MB progression and provide a strong rationale for using lnc-HLX-2-7 as a specific and potent therapeutic target for the group 3 MBs in children.